The Development of Mathematics Student Worksheets (LKS) Based on Problem Based Learning Approach with HOTS Questions - Sholahudin Al Ayubi (Universitas Islam Jember, 2019)
This study aims to develop Student Worksheets with Problem Based Learning (PBL) models based on High Order Thinking Skills (HOTS) questions on the subject of Building Square and Rectangular Flat. This type of research is development research that refers to the Thiagarajan 4-D Model. Data collection techniques using expert validation techniques, learning outcomes tests and questionnaires. The results showed that the worksheets that had been developed were valid, practical and effective with the validity coefficient of worksheets being 0.89 with very high criteria. Practical coefficient reached 92% with very good category and 85% effectiveness coefficient with good category. Student responses to learning activities and components of the worksheet are positive, reaching 95% of students happy with the teaching component. Keywords: Problem Based Learning (PBL), High Order Thinking Skills (HOTS)